Penerapan Komunikasi Organisasi dan Bisnis Model Canvas dalam Meningkatkan Kesejahteraan Kelompok Tani Belimbing Artha Mandiri Tulungagung Jawa Timur - Mochammad Sinung Restendy (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
Indonesia also has a tropical climate and one of the plants or fruits that are often found in this region is the sweet starfruit (Averrhoa carambola L.). The sweet starfruit plant is a fruit-bearing tree and is a horticultural plant cultivated in Indonesia, previously the type of starfruit tree originated from Malaysia, then spread widely to tropical countries, including Indonesia. This research is descriptive analysis with a qualitative approach for the Application of Organizational Communication and Business Model Canvas in Improving the Welfare of the Artha Mandiri Belimbing Farmer Group in Tulungagung, East Java. The main data was obtained from observations of interviews with the Artha Mandiri farmer group community. Secondary data was obtained from relevant literature related to the field of communication discussion, especially organizational communication. Data collection techniques were carried out through direct observation of what the community did.